Application of Technology Acceptance Model (TAM) to The Use of 3D Digital Design (Case Study Fashion Design Results of 2 Fashion Design Students at Jakarta State University) - Vivi Radiona Sofyani Putri; Melly Prabawati (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the acceptance of users, in this case, students majoring in Fashion Education at Jakarta State University, to the 3D Digital Design application, which is used in making the final project of the Fashion Design 2 course. The respondents in this study were Fashion Design Education students who had taken the Applied Computer and Fashion Design 2 courses. This study used quantitative research methods with quantitative descriptive data analysis techniques. The result of this study showed that media and technology could increase productivity, performance, and process efficiency in making 3D fashion designs for students.